Wunderlich syndrome – report of a rare case with comments on clinical implications - Krowiak, Karolina; Krowiak, Anita; Rajda, Sebastian; Palak, Artur; Balawender, Krzysztof (Publishing Office of the University of Rzeszow, 2024)
Introduction and aim. Spontaneous renal hemorrhage, known as Wunderlich syndrome, is a rare clinical condition that occurs without any history of trauma. The most common causes of this syndrome are both benign and malignant renal tumors. The treatment strategy is determined based on the patient’s hemodynamic stability. Description of the case. We report a case where a patient was admitted to the emergency department experiencing persistent pain in the right flank for three days. A diagnosis of spontaneous renal hemorrhage, secondary to an angiomyolipoma, was established through CT imaging. In this case study, we detail the diagnostic process and management of a patient who, due to the absence of hemodynamic instability, did not require surgical intervention. Instead, the patient was monitored and managed with conservative treatment. Conclusion. This case highlights the importance of prompt diagnosis, implementation of appropriate treatment, and the relevance of active follow-up in hemodynamically stable patients receiving conservative treatment.
Written informed consent for publication was obtained from the patient. We complied with the policy of the journal on ethical consent.
Keywords: angiomiolipoma; flank pain; renal hematoma; spontaneous renal hemorrhage; Wunderlich syndrome